2007
DOI: 10.1590/s0004-282x2007000400007
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of stroke among a brazilian urban population

Abstract: -Knowledge of the population in regards to stroke has clinical and epidemiological importance. Prompt identification of the symptoms means efficient medical attendance within the window of therapeutic opportunities reducing significantly the morbi-mortality. Our aim was to evaluate the level of knowledge of the population of Teresina (PI) concerning factors of risk, symptoms and treatment of stroke. The door-to-door study was carried out by means of a standardized application of questionnaire on risk factors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
28
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 19 publications
5
28
0
4
Order By: Relevance
“…These were expected findings because -with increasing age and level of education -the level of knowledge increases. These findings are consistent with previous studies [16][17][18][19][20][21][22] . Quick recognition of the symptoms would make adequate treatment possible and would minimize the unfavorable effects of stroke.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These were expected findings because -with increasing age and level of education -the level of knowledge increases. These findings are consistent with previous studies [16][17][18][19][20][21][22] . Quick recognition of the symptoms would make adequate treatment possible and would minimize the unfavorable effects of stroke.…”
Section: Discussionsupporting
confidence: 94%
“…Population-based studies have shown that there is a lack of knowledge about established stroke risk factors and warning signs in the USA [9,[11][12][13] , Australia [14] , South Korea [15] , Canada [16] , Brazil [17] , Oman [18] , India [19] and Turkey [20] . In Iran, the public's level of knowledge of symptoms and risk factors for stroke has not been studied so far.…”
mentioning
confidence: 99%
“…The socioeconomic level and lower level of education was independent factors associated with wrong answer in the question "what is a stroke". Other studies have also found this association 14,23 .…”
Section: Discussionsupporting
confidence: 54%
“…This observation could be corroborated by the lack of knowledge about stroke characteristics in the general population 10,11,14,15,23 . Even though a reasonable proportion of the participants of our study (70.5%) knew the definition of stroke, almost 30% of respondents did not know the answer (7.6%) or misidentified cerebrovascular disease with a heart or vascular disease (21.9%).…”
Section: Discussionmentioning
confidence: 93%
“…In a Brazilian study, hypertension was cited by 42.0% of the public [18] versus 24.0%, [19] 20.0% [20] and 51.0% [21] of respondents in India, UK and the USA, respectively. All this is in accordance with a multivariate model which demonstrated that hypertension was one of the most important risk factors for stroke [22].…”
Section: Discussionmentioning
confidence: 99%